Insights on Funeral Practices and Insects Associated With the Tombs of King Ferrante II d'Aragona and Other Renaissance Nobles. Issue 6 (4th July 2019) - Loni, Augusto; Fornaciari, Antonio; Canale, Angelo; Giuffra, Valentina; Vanin, Stefano; Benelli, Giovanni
Abstract: The impressive Sacristy of the Basilica of San Domenico Maggiore contains 38 wooden sarcophagi with the bodies of 10 Aragonese princes and other Neapolitan nobles, who died in the 15th and 16th centuries. To improve the knowledge about the entomofauna associated with bodies in archaeological contexts, herein we provide insights on the funerary practices and the insect community associated to Ferrante II King of Naples and other Italian Renaissance mummies of the Aragonese dynasty buried in the Basilica of St. Domenico Maggiore. We identified 842 insect specimens: 88% were Diptera (Muscidae, Fanniidae, and Phoridae), followed by 9% Lepidoptera (Tineidae) and 3% Coleoptera (Dermestidae and Ptinidae). Ninety-seven percent of the specimens were collected from the coffin of Francesco Ferdinando d'Avalos, which was the best preserved. A lack of fly species characterizing the first colonization waves of exposed bodies was noted. The most common fly was the later colonizing muscid Hydrotaea capensis (Wiedemann); only a few Fanniidae ( Fannia spp.) were retrieved. The lack of blowflies, coupled with recording H. capensis as the dominant fly, supports our hypothesis that corpses have been kept indoors for a long time under confined environmental conditions. Other explanations include odorous oils/balms having been used in the embalming process, causing the delay or stopping the arrival of first colonizer flies. Hermetically sealing of the coffin with bitumen may also have played a role in preventing access to the corpses. This scenario describes a historical context characterized by a well-advanced knowledge of body preparation, with specific burial techniques adopted for nobles.